Collection of thesis abstracts of master in community health - Noor Hassim Ismail (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Collection of Thesis Abstracts of Master In Community Health (Master in Community Health Sciences and Master in Medical Social Worker).